2008
DOI: 10.1016/j.jasms.2008.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric kinetic analysis of human tyrosylprotein sulfotransferase-1 and -2

Abstract: Protein tyrosine O-sulfation, a widespread post-translational modification, is mediated by two Golgi enzymes, tyrosylprotein sulfotransferase-1 and Ϫ2. These enzymes catalyze the transfer of sulfate from the universal sulfate donor 3=-phosphoadenosine-5=-phosphosulfate (PAPS) to the hydroxyl group of tyrosine residues to form tyrosine O-sulfate ester and PAP. More than 60 proteins have been identified to be tyrosine sulfated including several G protein-coupled receptors, such as CC-chemokine receptor 8 (CCR8) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 50 publications
1
29
0
Order By: Relevance
“…Non-radioactive assays using spectrophotometry and mass spectrometry have also been reported [166168]. Recently, Prather et al developed a universal phosphatase-coupled sulfotransferase assay.…”
Section: Sulfotransferases and Sulfationmentioning
confidence: 99%
“…Non-radioactive assays using spectrophotometry and mass spectrometry have also been reported [166168]. Recently, Prather et al developed a universal phosphatase-coupled sulfotransferase assay.…”
Section: Sulfotransferases and Sulfationmentioning
confidence: 99%
“…12 In contrast, Danan et al demonstrated that TPST2 is more catalytically efficient than TPST1 in sulfating CCR8 substrates. 15 The two tyrosylprotein sulfotransferases, TPST-1 and TPST-2, have overlapping but not identical substrate specificities in vitro and in vivo. 2,12,15 However, the relative abundances and distribution of the two isoenzymes have not yet been examined because of lack of suitable analytical reagents and tools.…”
Section: Introductionmentioning
confidence: 99%
“…15 The two tyrosylprotein sulfotransferases, TPST-1 and TPST-2, have overlapping but not identical substrate specificities in vitro and in vivo. 2,12,15 However, the relative abundances and distribution of the two isoenzymes have not yet been examined because of lack of suitable analytical reagents and tools. 10,12 Tyrosine-sulfated protein is important to cellular control, but no clear-cut acceptor sequence of TPSTs, which can be used to predict sulfotyrosine sites.…”
Section: Introductionmentioning
confidence: 99%
“…The Br signature in monobrominated peptide should be most evident for peptides up to around 1500 Da. For peptides over 2500 Da, the doublet shape of mono-brominated peptide completely disappears as the second isotopic peak originating from 13 C becomes stronger than the monoisotopic peak. Di-Br signature has a similar limitation.…”
Section: Limitations Of the Br Signaturementioning
confidence: 99%
“…First, tyrosine phosphorylation regulates protein's activity, localization, and interaction with other proteins in the cytosol [1][2][3]. Second, tyrosine sulfation modulates protein-protein interactions in the extracellular region [4][5][6][7][8][9], which is mediated by two tyrosyl protein sulfotransferases (TPST1 and TPST2) in the trans-Golgi network [10][11][12][13][14][15], resulting in many secretory proteins and Golgi membrane-anchored proteins being sulfated on tyrosine residues [16]. Tyrosine Oglycosylation has been recently investigated in the bacterial proteins [17,18].…”
mentioning
confidence: 99%